The Influence of Using E-Commerce, Locus of Control and Innovation on Business Performance of the Bengkalis Reseller Actors - Kartika Ayuni; Hutomo Atman Maulana (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
This study aims to analyze the effect of e-commerce usage, locus of control and innovation on the business performance of Bengkalis resellers. This study uses a quantitative method using a non-probability sampling method with purposive sampling. The sample in this study were 100 respondents, data processing using the IBM SPSS version 27 application with multiple linear regression analysis testing which includes validity test, reliability test, T test, F test, and coefficient of determination (R2). The results of this study indicate that: 1) The use of E-commerce has a positive and significant effect on the Business Performance of Bengkalis Resellers, 2) Locus of Control has a positive and insignificant effect on the Business Performance of Bengkalis Resellers, 3) Innovation has a positive and significant effect on the Business Performance of Bengkalis Resellers, 4) the coefficient of determination (R2) is 0.708. This means that the use of E-Cpmmerce, Locus of Control and Innovation affects the Business Performance of Bengkalis Reseller Actors by 70.8% while the remaining 29.2% is influenced by other variables not examined in this study.